THE ASSOCIATION BETWEEN PHYSIOLOGIC DEAD-SPACE FRACTION AND MORTALITY IN PATIENTS WITH THE ACUTE RESPIRATORY DISTRESS SYNDROME ENROLLED INTO A PROSPECTIVE MULTI-CENTERED CLINICAL TRIAL - Kallet, Richard H (2013)
OBJECTIVE: To test the association between pulmonary dead-space fraction (V(D)/V(T)) and mortality in patients with ARDS (Berlin Definition, PaO(2)/FiO(2) ≤ 300 mm Hg; PEEP ≥ 5 cm H(2)O) enrolled into a clinical trial incorporating lung-protective ventilation. DESIGN: Prospective, multi-center study. SETTING: Medical-surgical intensive care units in the United States. SUBJECTS: 126 ALI patients enrolled into a phase III randomized, placebo-controlled study of aerosolized albuterol. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: V(D)/V(T) and pulmonary mechanics were measured within 4 hours of enrollment and repeated daily on study days 1 and 2 in subjects requiring arterial blood gases for clinical management. At baseline, non-survivors had a trend towards higher V(D)/V(T) compared to survivors (0.62 ± 0.11 vs. 0.56 ± 0.11 respectively, p = 0.08). Differences in V(D)/V(T) between non-survivors and survivors became significant on study days 1 (0.64 ± 0.12 vs. 0.55 ± 0.11 respectively, p = 0.01) and 2 (0.67 ± 0.12 vs. 0.56 ± 0.11 respectively, p=0.004). Likewise, the association between V(D)/V(T) and mortality was significant on study day 1 (odds ratio per 0.10 change in V(D)/V(T) [95% confidence interval]: 6.84 [1.62–28.84] p = 0.01; and study day 2: 4.90 [1.28–18.73] p = 0.02) after adjusting for V(D)/V(T), PaO(2)/FiO(2), oxygenation index, vasopressor use and the primary risk for ARDS. Using a Cox proportional hazard model, V(D)/V(T) was associated with a trend towards higher mortality (HR = 4.37 [CI: 0.99 – 19.32]; p = 0.052) that became significant when the analysis was adjusted for daily oxygenation index (HR = 1.74 [95% CI: 1.12 – 3.35] p = 0.04). CONCLUSIONS: Markedly elevated V(D)/V(T) (≥ 0.60) in early ARDS is associated with higher mortality. Measuring V(D)/V(T) may be useful in identifying ARDS patients at increased risk of death who are enrolled into a therapeutic trial.